The Exchange of Bibliographic Data and the MARC Format : Proceedings of the International Seminar on the Marc Format and the Exchange of Bibliographic Data in Machine Readable Form. Sponsored by the Volkswagen Foundation, Berlin, June 14th–16th 1971 - Berlin, West> International Seminar on the MARC Format and the Exchange of bibliographic Data in Mac; West> Arbeitsstelle für Bibliothekstechnik <Berlin (De Gruyter, 1973)
No detailed description available for'The exchange of bibliographic data and the MARC format'.